Studies on Novel Bisaryl Hydrazino-s-triazine Derivatives - Part 2 - J. A. Chaudhari; R. P. Patel; M. V. Hathi (E-Journal of Chemistry)
Various 2(4-chloro phenyloxy)-4,6-bisarylhydrazino-1,3,5-triazines(3a-f) were prepared by reaction of 2(4-chloro phenyloxy)-4,6-dichloro -1,3,5-triazine and various aryl hydrazine derivatives. All the 3a-f derivatives were characterized by elemental analysis and IR spectral studies. All the compounds were screened for microbial activity against gram-positive and gram-negative bacteria.